A LiF-Pie-Structured Interphase for Silicon Anodes - Li, Weiping; Xu, Shiwei; Zhong, Cong; Fang, Qiu; Weng, Suting; Ma, Yinzi; Wang, Bo; Li, Yejing; Wang, Zhaoxiang; Wang, Xuefeng (Nano-Micro Letters, 2025)
Silicon (Si) is a promising anode material for rechargeable batteries due to its high theoretical capacity and abundance, but its practical application is hindered by the continuous growth of porous solid-electrolyte interphase (SEI), leading to capacity fade. Herein, a LiF-Pie structured SEI is proposed, with LiF nanodomains encapsulated in the inner layer of the organic cross-linking silane matrix. A series of advanced techniques such as cryogenic electron microscopy, time-of-flight secondary ion mass spectrometry, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry have provided detailed insights into the formation mechanism, nanostructure, and chemical composition of the interface. With such SEI, the capacity retention of LiCoO2||Si is significantly improved from 49.6% to 88.9% after 300 cycles at 100 mA g−1. These findings provide a desirable interfacial design principle with enhanced (electro) chemical and mechanical stability, which are crucial for sustaining Si anode functionality, thereby significantly advancing the reliability and practical application of Si-based anodes. Article Highlights: 1 A novel hierarchical solid electrolyte interface (SEI) structure is developed, featuring a lithium fluoride (LiF)-rich inner layer and a silane-based cross-linked matrix. 2 A comprehensive suite of advanced characterization techniques provides multi-scale insights into the structural and chemical composition of the LiF-Pie SEI. 3 The proposed SEI design significantly enhances cycling stability, achieving a capacity retention of LiCoO2||Si increase from 49.6% to 88.9% after 300 cycles at a current density of 100 mA g−1.